Βουργάρο και Παραδείσι: Δυο Ανδριώτικα μετόχια στην Αλώνη - Πολέμης Δημήτριος I. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1986)
In the small island of Halone (now Pa§a Liman Adasr) in the Sea of Marmara there were to be found several properties belonging to large monasteries of Greece proper which had been administered in the traditional manner as metochia. The paper concerns two such metochia. comprising of several properties each, that since the 18th century had been linked with the monastery of St. Nicholas in the island of Andros. The first such property -no more than a small field- we hear of was dedicated to the monastery in 1723, and in the course of the following years other properties were added to it so that by 1767 they were all grouped to form the metochion of Voulgaron. These little plots of land were mostly vineyards, wine being the main produce of Halone. In the meantime the local monastery of St. Parasceve at Paradeisi, the most important on the island, came to be faced with serious financial difficulties and was in heavy debts. Eventually it was felt that it could hardly survive independently, and in 1790 the local community of the whole island (which incidentally was inhabited almost entirely by Greeks) and the Metropolitan of Proikonnesos, who had then his residence on the island, came into an agreement with Neilos Palaiologos (a monk of St. Nicholas in charge of the metochion of Voulgaron) as a result of which St. Parasceve became also a metochion of St. Nicholas. Thus the larger monastery of Andros undertook to repay the debts, to administer the smaller monastery and its properties at Halone and also to provide badly needed monks for this administration. This state of affairs continued up to 1922 when all Christian population of Halone was compelled to emigrate. At periods the relationship between the monks of St. Nicholas and the people of Halone was difficult and was especially so after the middle of the 19th century when monasticism in Greece proper was undergoing a period of decline. Destructive disease of the local vineyards also contributed to the sad state of affairs. Arbitrary seizures of land, litigations and appeals to the Patriarchate of Constantinople are constant features of this period. A rather extensive collection of archival material is preserved in the monastery of St. Nicholas, and out of these 70 relevant documents are published. This rich documentation not only illustrates the history of the two metochia but also provides information on the conditions on the island and in general serves as source material for customs, place-names, names of persons etc. which is valuable in view of the fact that other archival material on Halone may not be in existence elsewhere.